Pengaruh Pelatihan, Budaya Kerja Dan Kepemimpinan Inklusif Terhadap Kinerja Karyawan PT. Bank X (Persero) Tbk. - Anggraini, Diah Ayu; Djaelani, Abdul Kodir; Slamet, Afi Rachmat (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to examine the effect of training, work culture, and inclusive leadership on employee performance at PT. Bank X (Persero) Tbk. The research method used is quantitative with an explanatory approach. Data were collected through questionnaires distributed to 60 respondents using a saturated sampling technique. The data analysis techniques employed include multiple linear regression. The results indicate that training, work culture, and inclusive leadership simultaneously have a significant effect on employee performance. Partially, each of these variables also has a significant individual effect. These findings confirm that improving human resources through training, fostering a positive work culture, and implementing inclusive leadership are crucial to enhancing employee performance in the banking sector. Keywords: Training, Work Culture, Inclusive Leadership, Employee Performance.